Analisis Keuangan Untuk Nilai Tambah Pasar di Industri Digital - Teni Eriyanti; Dwi Urip Wardoyo (Jurnal Mahasiswa: Jurnal Ilmiah Penalaran dan Penelitian Mahasiswa, 2023)
With the growth of internet users providing added value to the infrastructure of telecommunications sub-sector companies, companies are required to create better performance. This study aims to analyze profitability, leverage, and dividend policy on company added value using MVA in telecommunications sub-sector companies during the 2017–2022 period. The analytical method in this study uses panel data regression using 7 companies, so the total sample is 42 telecommunications companies. This test was carried out using Eviews version 12. The results showed that Return on Equity (ROE), debt-to-equity ratio (DER), and Dividend Policy using dummy variables simultaneously affect the added value of companies using Market Value Added (MVA). Return on Equity (ROE) has an effect on market-added value by using Market Value Added (MVA) and debt-to-equity ratio (DER), and Dividend Policy has no partial effect on Market Value Added (MVA). The research results are expected to contribute both to the literature and to practice. Companies can increase their added value by paying attention to their profitability ratios. Investors pay attention to company reports to measure company performance so as to increase the company's added value.